Calcitriol-Mediated Hypercalcemia, Somatostatin Receptors Expression and 25-Hydroxyvitamin D3-1α- Hydroxylase in GIST Tumors - Herrera-Martínez, Yiraldine; Contreras González, María José; Pedraza-Arévalo, Sergio; Guerrero Martínez, Maria del Carmen; Rodrigo Martínez, Ángela; González Menchen, Alberto; Blanco Molina, Maria Angeles; Gálvez-Moreno, Maria Angeles; Moreno-Vega, Alberto L.; Luque, Raúl M.; Herrera-Martínez, Aura D. (Frontiers in Endocrinology, 2022)
Hypercalcemia is a common complication in cancer patients Mainly caused by Parathyroid hormone-related protein (PTHrP) secretion and metastasis. Calcitriol secretion is a rare source of hypercalcemia in solid tumors, especially in gastrointestinal stromal tumors (GIST). We present a case report of a female patient with a 23 cm gastric GIST that expressed somatostatin-receptors and presented with severe hypercalcemia due to calcitriol secretion. Calcium control was achieved with medical treatment before the use of targeted-directed therapies. Surgery was performed and allowed complete tumor resection. Two years later, patient remains free of disease. Molecular analysis revealed the mRNA expression of 25-hydroxyvitamin D3-1-hydroxylase (1αOHase) and vitamin-D receptors in the tumor cells, confirming the calcitriol-mediated mechanism. Furthermore, the expression of the endotoxin recognition factors CD14 and TLR4 suggests an inflammatory mediated mechanism. Finally, the expression of somatostatin-receptors, especially SST2 might have been related with clinical evolution and prognosis in this patient.